Estimates and determinants of sexual violence against women in the Democratic Republic of Congo - Peterman, Amber; Palermo, Tia; Bredenkamp, Caryn (American Public Health Association, 2011)
Objectives. We sought to provide data-based estimates of sexual violence in the Democratic Republic of Congo (DRC) and describe risk factors for such violence.Methods. We used nationally representative household survey data from 3436 women selected to answer the domestic violence module who took part in the 2007 DRC Demographic and Health Survey along with population estimates to estimate levels of sexual violence. We used multivariate logistic regression to analyze correlates of sexual violence.Results. Approximately 1.69 to 1.80 million women reported having been raped in their lifetime (with 407 397–433 785 women reporting having been raped in the preceding 12 months), and approximately 3.07 to 3.37 million women reported experiencing intimate partner sexual violence. Reports of sexual violence were largely independent of individual-level background factors. However, compared with women in Kinshasa, women in Nord-Kivu were significantly more likely to report all types of sexual violence.Conclusions. Not only is sexual violence more generalized than previously thought, but our findings suggest that future policies and programs should focus on abuse within families and eliminate the acceptance of and impunity surrounding sexual violence nationwide while also maintaining and enhancing efforts to stop militias from perpetrating rape.